2017
DOI: 10.54865/mjas1771-2057n
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Effect of Dry Extract of Tribulus Terrestris on Liver’s Histostructure of Guinea Fowl and Japanese Quail

Abstract: A comparative study of the effect of the Bulgarian product Vemo Herb (dry extract of Tribulus terrestris) produced on the histological structure of liver in Guinea fowl (Numida meleagris) and Japanese quail (Coturnix coturnix japonica) was carried out with 2 groups (control and experimental) from both poultry species: 15 Pearl-gray Guinea fowls (12 females and 3 males) per group, and 17 Japanese quails -Pharaon breed (13 females and 4 males) per group. The poultry in the experimental groups received 10 mg/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Results indicated that significant improvements were observed concerning the productive performance of the layer treated with dry extract of T. terrestris at a dose of 10 mg/kg body weight. Guinea fowls and quails exhibit moderate to severe fatty infiltration and liver degeneration, mainly in the males of both species [ 134 ]. Nikolova et al [ 135 ] explored how different doses of T. terrestris dry extract affected egg production, testosterone levels in the blood, and the histological structure of the gonads and kidneys in Japanese quail.…”
Section: Immuno-modulatory Effects Of T Terrestrismentioning
confidence: 99%
“…Results indicated that significant improvements were observed concerning the productive performance of the layer treated with dry extract of T. terrestris at a dose of 10 mg/kg body weight. Guinea fowls and quails exhibit moderate to severe fatty infiltration and liver degeneration, mainly in the males of both species [ 134 ]. Nikolova et al [ 135 ] explored how different doses of T. terrestris dry extract affected egg production, testosterone levels in the blood, and the histological structure of the gonads and kidneys in Japanese quail.…”
Section: Immuno-modulatory Effects Of T Terrestrismentioning
confidence: 99%
“…Разработка рецептур искусственных питательных сред для кормления гусениц тутового шелкопряда остается актуальным направлением исследований по настоящее время. Компонентами искусственных диет являются высушенные листья шелковицы, различные виды зерновой и соевой муки, крахмал, целлюлоза, агар-агар, сахароза, растительные масла, минеральные вещества, органические кислоты, витамины, фитостерол, антибиотики и консерванты (Moise et al 2020;Nikolova 2020).…”
Section: Introductionunclassified